Bible Proverbs on dialogue as a method of problem solving - Acuña Casas, Raúl (2012)
It is based on dialogue as a method between teacher and student where bothinteract to understand and solve problems related to real situations of natural andsocial environment, and in a new stage characterized by system research, and thesupport of Trans disciplinary theories that help us understand the complexity ofthings. We also touch mechanics of dialogue and logical structure that sustains.Finally, it is raised with the implications from a set of biblical proverbs that enrichthe efficiency of dialogue as a method to formulate equations or relationships toinvolve all the conditions of the problem